Understanding Network Hacks Attack and Defense with Python - Ballmann, Bastian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book explains how to see one's own network through the eyes of an attacker, to understand their techniques and effectively protect against them. Through Python code samples the reader learns to code tools on subjects such as password sniffing, ARP poisoning, DNS spoofing, SQL injection, Google harvesting and Wifi hacking. Furthermore the reader will be introduced to defense methods such as intrusion detection and prevention systems and log file analysis by diving into code.
Installation -- Networks 4 newbies -- Python Basics -- Layer 2 attacks -- TCP / IP Tricks -- WHO IS DNS? -- HTTP Hacks -- Wifi fun -- Feeling Bluetooth on the Tooth -- Bargain Box Kung Fu -- Scapy Reference -- Secondary Links -- Index.
Keywords: Computer science; Computer communication systems; Software engineering; Programming languages (Electronic computers).; Computer security; Computer engineering; Computer Science; Computer Communication Networks; Computer Engineering; Systems and Data Security; Programming Languages, Compilers, Interpreters; Software Engineering; Software Engineering/Programming and Operating Systems; Electronic books